2008
DOI: 10.1098/rspb.2008.1570
|View full text |Cite
|
Sign up to set email alerts
|

Honest sexual signalling mediated by parasite and testosterone effects on oxidative balance

Abstract: Extravagant ornaments evolved to advertise their bearers' quality, the honesty of the signal being ensured by the cost paid to produce or maintain it. The oxidation handicap hypothesis (OHH) proposes that a main cost of testosterone-dependent ornamentation is oxidative stress, a condition whereby the production of reactive oxygen and nitrogen species (ROS/RNS) overwhelms the capacity of antioxidant defences. ROS/RNS are unstable, very reactive by-products of normal metabolic processes that can cause extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
94
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 40 publications
(76 reference statements)
9
94
0
Order By: Relevance
“…Consistent with our results, a recent study on red grouse found that the size of a similar carotenoid-based ornament before an experimental parasite infection predicted the magnitude of the subsequent change in parasite-induced oxidative damage (Mougeot et al, 2009a). Again, in red-legged partridges, eye ring coloration also revealed the individual's capacity to endure oxidative challenges in the past, as partridges maintaining redder eye rings at the end of reproduction were also those with less oxidative damage (TBARS) at that time (Alonso-Alvarez et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with our results, a recent study on red grouse found that the size of a similar carotenoid-based ornament before an experimental parasite infection predicted the magnitude of the subsequent change in parasite-induced oxidative damage (Mougeot et al, 2009a). Again, in red-legged partridges, eye ring coloration also revealed the individual's capacity to endure oxidative challenges in the past, as partridges maintaining redder eye rings at the end of reproduction were also those with less oxidative damage (TBARS) at that time (Alonso-Alvarez et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…However, previous studies have reported an increase in oxidative stress associated with a PHA immune challenge (Costantini and Dell'Omo, 2006;Hõrak et al, 2007), supporting the existence of an oxidative cost associated with the cell-mediated immune response (Costantini and Møller, 2009;Sorci and Faivre, 2009). Parasite challenges and infections were also shown to increase oxidative damage in another gallinacean, the red grouse Lagopus lagopus scoticus (Mougeot et al, 2009a;Mougeot et al, 2010), consistent with the idea that raising an immune response increases oxidative stress.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This method has already been described and used successfully in several studies (e.g. Mougeot et al, 2009;Losdat et al, 2011b).…”
Section: Oxidative Damagementioning
confidence: 99%
“…This has been shown in lekking species such as black grouse Tetrao tetrix, in which males with bigger combs achieve greater mating success (Rintamaki et al 2000), as well as in monogamous species, such as the rock ptarmigan Lagopus mutus (Bart and Earnst 1999) or the red grouse Mougeot et al 2007Mougeot et al , 2009, in which males with bigger combs hold larger territories, are dominant and preferred by females. A main parasite of red grouse is the nematode Trichostrongylus tenuis, which has well documented negative impacts on this host (Martinez-Padilla et al 2014), reducing condition and comb size in both males (Mougeot et al 2005a(Mougeot et al , 2009 and females (Martinez-Padilla et al 2011). We sampled social pairs on three study sites before laying and reduced T. tenuis parasite abundance in some females using an anthelminthic treatment.…”
Section: Introductionmentioning
confidence: 99%